Project Management tools and related learning perspective. Preliminary reflections - Erina Guraziu (Firenze University Press, 2020)
Projects are unique by nature. They are born to introduce change through a transdisciplinary, cross-functional and, usually, multicultural organization, composed out of people with different competences who work together for project life span. The Project Management ensures that projects achieve objectives, results, change and benefits. All projects generate learning, thanks to the transformation of experience into knowledge (Kolb, 1984), but the Project Management method, PRINCE2, may be considered as a valid tool for developing a training project, focused on the achievement of learning outcomes, because it allows to describe their quality requirements, to register the change brought and to measure the connected benefits related to employability. The article starts with the definition of Project Management, enters later into more details in the PRINCE2 method and finally approaches the learning value that the product-based planning may represent in the context of non-formal and informal learning, but also in a formal educational one, in order to enhance achieved learning outcomes.   Strumenti di Project Management per la formazione. Una riflessione introduttiva I progetti sono unici per natura. Nascono per introdurre cambiamento attraverso un'organizzazione interdisciplinare, cross-funzionale e, spesso, multiculturale, composta da persone con diverse competenze che lavorano insieme nell'arco di vita progettuale delimitato. Il Project Management è la tecnica che garantisce al progetto il raggiungimento dei suoi obiettivi, producendo risultati, cambiamento e benefici. Tutti i progetti generano apprendimento, grazie alla trasformazione dell'esperienza in conoscenza (Kolb, 1984), ma il metodo di Project Management, PRINCE2, può essere considerato come un valido strumento per sviluppare un progetto formativo, finalizzato al raggiungimento di risultati di apprendimento, in quanto permette di descriverne i requisiti qualitativi, registrare il cambiamento e misurare i benefici connessi all'employability. L'articolo parte dalla definizione del concetto di Project Management, per entrare nel dettaglio del metodo PRINCE2 e approcciare il valore apprenditivo che una pianificazione basata sul risultato può rappresentare nei contesti di apprendimento informali e non-formali, ma anche in quelli di educazione formale, al fine di valorizzare i risultati di apprendimento raggiunti.